Hasil Pemeriksaan Laboratorium Forensik Terhadap Tulang Kerangka Sebagai Salah Satu Alat Bukti Surat - Benny Haninta Surya (Sebelas Maret University, 2017)
Skeleton founded case in Pinang Sebatang Timur Village, Tualang, Siak by law enforcement officer with any help from expert had been discovered a fact which said that the skeleton were had been found is a human bone, and then law enforcement officer found another facts and evidences that leading to the murderer case. with further examination with evidence both have found by the law enforcement officerand the Visum et Repertum examination on skeleton result by the expert, Dita Desmala Sari, the defendant then applied a Planned Murder Crime by the judge. The result shows that first the result of forensic laboratory in skeleton examination is a evidence made from knowledge and examination by Expert, precisely Forensic Expert or Medical Expert Judiciary, but it’s categorized in a documentary evidence based on Article 184 (1) KUHAP jo. Article187 letter c KUHAP. Second, the result of forensic laboratory in skeleton examination considered by the judges as one of the valuation from the unsure on the Planned Murder Crime and also being Judges “Conviction Adder” to give Death Punishment for the defendant based on his fault which rated too nasty for a human being and absolutely cannot be tolerated anymore has been matched to Article 183 jo. Article 193 (1) of KUHAP. Keywords: Forensic Laboratory, Evidence, Planned Murder Crime